The use of human amniotic fluid mesenchymal stem cells as the feeder layer to establish human embryonic stem cell lines. (4th March 2013) - Soong, Yung‐Kwei; Huang, Shang‐Yu; Yeh, Chiu‐Hsiang; Wang, Tzu‐Hao; Chang, Kuo‐Hsuan; Cheng, Po‐Jen; Shaw, S. W. Steven
Abstract: Human embryonic stem cells (hESCs) are pluripotent cells that have the potential to differentiate into the three germ layers and possibly all tissues of the human body. To fulfil the clinical potentials for cell‐based therapy, banks of hESC lines that express different combinations of the major histocompatibility genes should be established, preferably without exposing such cells to animal cells and proteins. In this study, we tested human amniotic fluid mesenchymal stem cells (AFMSCs) as feeder cells to support the growth of hESCs. Our results indicated that mitomycin‐treated AFMSCs were able to support the newly established hESC lines CGLK‐1 and CGLK‐2. The hESC colonies cultured on AFMSCs expressed alkaline phosphatase (ALK‐P), SSEA‐4, TRA‐1‐60, TRA‐1‐81, Oct‐4, Nanog and Sox‐2, which are markers for undifferentiated hESCs. Chromosomal analyses of both hESC lines, CGLK‐1 and CGLK‐2, which were cultured on AFMSC feeders for 22 and 14 passages, respectively, were confirmed to be normal karyotypes (46, XX). The ability of AFMSCs as feeder cells to maintain the undifferentiated growth and pluripotency of hESCs was confirmed by in vivo formation of teratomas derived on AFMSC hESCs in severe combined immune‐compromised mice. The use of AFMSCs for feeder cells to culture hESCs has several advantages, in that AFMSCs are not tumourigenic and can be expanded extensively with a short doubling time. Copyright © 2013 John Wiley & Sons, Ltd.